Lung Organoids—The Ultimate Tool to Dissect Pulmonary Diseases? - Bosáková, Veronika; De Zuani, Marco; Sládková, Lucie; Garlíková, Zuzana; Jose, Shyam Sushama; Zelante, Teresa; Hortová Kohoutková, Marcela; Frič, Jan (Frontiers in Cell and Developmental Biology, 2022)
Organoids – the 3D in vitro model recently provided an excellent tool to address molecular processes and pathology of human organs. Organoids can be derived from a variety of cell types, such as human primary progenitor cells, pluripotent stem cells, or tumour-derived cells, and provide a comprehensive model for many human organs. Here we focus on the development of 3D lung organoids and their further use as disease models across many pathologies. We introduce various experimental approaches used to model complex human diseases and analyse their advantages and disadvantages. We also discuss the validation of the organoids and their physiological relevance to the study of lung diseases. Furthermore, we summarize the current use of lung organoids as a model for host-pathogen interaction and human lung diseases such as cystic fibrosis, chronic obstructive pulmonary disease, or SARS-CoV-2 infection. Moreover, we discussed the lung organoids derived from tumour cells – tumouroids – as lung cancer models and their use in personalized cancer medicine research. Finally, we outline the future of research in the field of human iPSC-derived organoids.